(3GdVhA TQM GdeUHGMs - (3JGL GdOjf eMeO Hf eMeO GdCSaQGjfis ((3eMeO Hf bGdhf GdERdhi s)
(3ChdgG (B:s
(3Ef CMb eG jJhTM HPcQg UOhQ GdcJH hGdOaGJQ hjJhaQ Ydi fTQg GdSfI GdHGOi hGdMGVQ MeO Gddg SHMGfg hJYGdi s
(3BNQgG (B:s
(3dCf EgGfI Gdehdi ef dhGRe VQH GdZdGe hgPG HGH ddEWfGH hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3hbO GSJNQLg GdeDda ef cJGH GdCbdjO TQM GdeaUd ddEeGe GdReNTQis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B348 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B71 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B488s
Keywords: (3GdfMhs